Resin composition, carbon material dispersion composition, composite slurry, electrode film, secondary battery, and vehicle

A resin composition with a copolymer and alkali metal improves carbon material dispersibility, enhancing electrode conductivity and adhesion, resulting in secondary batteries with improved rate and cycle characteristics for vehicle applications.

JP7620693B1Active Publication Date: 2025-01-23TOYO INK MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023221779
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-01-23
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

Existing methods for dispersing carbon materials in secondary battery electrodes face challenges in achieving both good dispersibility and electrode properties, leading to poor conductivity and adhesion, which affects the battery's rate and cycle characteristics.

Method used

A resin composition containing a copolymer with specific structural units and an alkali metal within a defined range is used to create a carbon material dispersion composition, ensuring excellent dispersibility and conductivity, thereby improving electrode film quality and secondary battery performance.

Benefits of technology

The solution results in secondary batteries with enhanced rate characteristics, cycle characteristics, and safety, suitable for use in vehicles requiring high capacity and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620693000001
    Figure 0007620693000001
  • Figure 0007620693000002
    Figure 0007620693000002
  • Figure 0007620693000003
    Figure 0007620693000003
Patent Text Reader

Abstract

To provide a resin composition and a carbon material dispersion composition which can achieve both good dispersibility and good electrode properties, a composite slurry which can obtain an electrode film having high conductivity and adhesion, and more specifically, a secondary battery having excellent rate characteristics and cycle characteristics, and a vehicle having the secondary battery, which is safe and has improved fuel efficiency. The present invention provides a resin composition containing a copolymer (X) having an alkylene structural unit and a nitrile group-containing structural unit, and an alkali metal, The content of the alkali metal is 50 ppm or more and less than 10,000 ppm, The problem is solved by a resin composition, characterized in that the resistivity of the resin composition when the non-volatile content is adjusted to 8 mass% with N-methyl-2-pyrrolidone is 5,000 Ω cm or more and 25,000 Ω cm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a carbon material dispersion composition. More specifically, the present invention relates to a carbon material dispersion composition containing a resin composition and a carbon material, a composite slurry containing the carbon material dispersion composition and an active material, an electrode film formed by coating them, a secondary battery including an electrode having an electrode film and an electrolyte, and a vehicle including the secondary battery. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, there is a demand for secondary batteries with high energy density and further for high capacity of the secondary batteries. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] The negative electrode materials used in these lithium-ion secondary batteries are carbon materials such as graphite, which have a large charge / discharge capacity per unit mass at a base potential close to that of lithium (Li). However, these electrode materials are used to the extent that the charge / discharge capacity per mass is close to the theoretical value, and the energy density per mass of the battery is approaching its limit. Therefore, in order to increase the utilization rate of the electrode, studies are being conducted to reduce the conductive additives and binders that do not contribute to the discharge capacity.

[0004] The conductive additive plays a role in forming a conductive path inside the electrode, and is required to be resistant to breakage due to the expansion and contraction of the electrode film. In order to maintain the conductive path with a small amount of conductive additive, it is effective to use a carbon material with a large specific surface area, in particular carbon nanotubes (CNTs), which are a type of nanocarbon. However, carbon materials with a large specific surface area have a strong cohesive force, which makes it difficult to disperse them uniformly in the composite slurry or electrode film.

[0005] In view of this background, many methods have been proposed in which a carbon material dispersion composition is prepared using various dispersants, and a composite slurry is produced via the carbon material dispersion composition.

[0006] For example, Patent Documents 1 and 2 propose carbon material dispersion compositions with improved dispersibility by adding a basic compound together with a polymer-based dispersant such as polyvinylpyrrolidone or hydrogenated nitrile rubber. However, while these dispersants can produce carbon material dispersion compositions in a good dispersion state, they can sometimes result in poor dispersion of the carbon material in the process of forming an electrode film, resulting in poor conductivity.

[0007] In addition, in Patent Documents 3 and 4, a predetermined Mooney viscosity (ML 1+4 It has been proposed that the use of an electrode binder composition containing hydrogenated nitrile rubber having a specific surface area of ​​190,000 to 210,000 g / mol enables the carbon material to be dispersed well in the composite slurry. Patent Document 5 proposes the use of a dispersant composition containing hydrogenated nitrile rubber having a weight average molecular weight of 190,000 to 210,000 g / mol. However, these dispersants have low dispersing ability, making it difficult to disperse carbon materials with large specific surface areas at high concentrations.

[0008] Therefore, Patent Document 6 proposes a technology that uses a copolymer having a specific structural unit and molecular weight as a dispersant to disperse a carbon material well in a solvent and maintain a good dispersion state when preparing a composite slurry and when producing an electrode film. However, a large amount of base needs to be added to obtain a specific structure, and this causes problems such as a decrease in the molecular weight of the dispersant and a decrease in electrode strength due to deterioration of the binder resin. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2014-181140 A [Patent Document 2] Korean Patent No. 10-1831562 [Patent Document 3] Patent No. 6848862 [Patent Document 4] Patent No. 6863278 [Patent Document 5] Special Publication No. 2022-536304 [Patent Document 6] Patent Publication No. 2021-122751 Summary of the Invention [Problem to be solved by the invention]

[0010] The problem to be solved by the present invention is to provide a resin composition and a carbon material dispersion composition that can achieve both good dispersibility and good electrode properties. Also, the problem to be solved by the present invention is to provide a composite slurry that can obtain an electrode film with high conductivity and adhesion, more specifically, a secondary battery with excellent rate characteristics and cycle characteristics, and a vehicle with high safety and improved fuel efficiency by using the secondary battery. [Means for solving the problem]

[0011] The inventors of the present invention have conducted extensive research to solve the above problems, and have found that the above problems can be solved by a resin composition that contains a copolymer (X) having a specific structure and an alkali metal in an amount of 50 ppm or more and less than 10,000 ppm, and that has a resistivity in a specific range when the non-volatile content is adjusted to 8 mass% with N-methyl-2-pyrrolidone.

[0012] That is, the present invention includes the following embodiments, but the embodiments of the present invention are not limited to the following. [1] A resin composition containing a copolymer (X) having an alkylene structural unit and a nitrile group-containing structural unit, and an alkali metal, The content of the alkali metal is 50 ppm or more and less than 10,000 ppm, A resin composition, characterized in that the resistivity of the resin composition when the non-volatile content is adjusted to 8 mass% with N-methyl-2-pyrrolidone is 5,000 Ω·cm or more and 25,000 Ω·cm or less. [2] The resin composition according to [1], wherein the Z-average molecular weight of the copolymer (X) is 20,000 or more and 200,000 or less. [3] The resin composition according to [1] or [2], wherein the ratio (Mz / Mw) of the Z-average molecular weight (Mz) to the weight-average molecular weight (Mw) of the copolymer (X) is 2.0 or less. [4] A carbon material dispersion composition comprising the resin composition according to any one of [1] to [3] and a carbon material. [5] A composite slurry comprising the carbon material dispersion composition according to [4] and an active material. [6] An electrode film obtained by coating the composite slurry according to [5]. [7] A secondary battery comprising an electrode having the electrode film according to [6] and an electrolyte. [8] A vehicle equipped with the secondary battery described in [7]. Effect of the Invention

[0013] The resin composition of the present invention has excellent dispersibility of dispersed substances such as carbon materials, and by using a carbon material dispersion composition containing this resin composition, an electrode film having excellent conductivity and adhesion can be obtained. In addition, a secondary battery having excellent rate characteristics and cycle characteristics can be obtained. As a result, it can be suitably used even in vehicle applications such as hybrid automobiles, plug-in hybrid automobiles, and electric automobiles, in which high capacity, high output, and high durability are required for the secondary battery to be mounted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The resin composition, carbon material dispersion composition, composite slurry, electrode film, and secondary battery of the present invention will be described in detail below, but are not limited thereto. Note that the numerical values ​​specified in this specification are values ​​obtained by the methods disclosed in the embodiments or examples.

[0015] In addition, in this specification, a numerical range specified using "to" is intended to include the numerical values ​​before and after "to" as the lower and upper limit values ​​of the range.

[0016] In this specification, "N-methyl-2-pyrrolidone" may be abbreviated as "NMP," "carbon black" as "CB," "carbon nanotubes" as "CNT," and "carbon material dispersion composition" as "dispersion composition." The non-volatile content refers to the solid content excluding the solvent, and can be determined by measuring the content of the residue remaining after the solvent volatilizes or evaporates when the resin composition is heated at or above the boiling point of the solvent contained therein.

[0017] In the embodiment of the present invention, the resin composition refers to a state before the carbon material and the electrode active material are added, and the carbon material dispersion composition refers to a state before the electrode active material is added. In this respect, the resin composition and the carbon material dispersion composition are distinguished from a composite slurry containing an electrode active material. Furthermore, this concept excludes a state in which a carbon material and an electrode active material are intentionally added to a resin composition, and the amount of the carbon material and the electrode active material may be 1 mass% or less, 0.5 mass% or less, or 0.1 mass% or less, based on the amount of non-volatile components of the resin composition (100 mass%), or may be 0 mass%. Furthermore, this is a concept that excludes a state in which an electrode active material is intentionally added to a carbon material dispersion composition, and the amount of the electrode active material may be 1 mass% or less, 0.5 mass% or less, or 0.1 mass% or less, based on the amount of non-volatile components in the carbon material dispersion composition (100 mass%), or it may be 0 mass%. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a mixture of two or more types. The numerical values ​​specified in this specification are values ​​determined by the methods disclosed in the embodiments or examples.

[0018] ≪Resin composition≫ The resin composition of the present embodiment contains at least a copolymer (X) having an alkylene structural unit and a nitrile group-containing structural unit, and an alkali metal. The content of the alkali metal is 50 ppm or more and less than 10,000 ppm, and the resistivity of this resin composition when the non-volatile content is adjusted to 8 mass % with N-methyl-2-pyrrolidone is 5,000 Ω·cm or more and 25,000 Ω·cm or less. By using such a resin composition, a dispersion composition having excellent dispersibility of the dispersed material and good stability can be obtained. In particular, when the dispersed substance is a carbon material, a carbon material dispersion composition having excellent dispersibility and oxidation resistance can be obtained, and since the composition also has excellent electrical conductivity, a secondary battery using the composition can have excellent rate characteristics and high-temperature cycle characteristics.

[0019] As the material to be dispersed, any of conventionally known inorganic pigments, organic pigments, etc. can be used in addition to the carbon materials described below, but it is particularly effective for carbon materials.

[0020] Examples of inorganic pigments include metal powders such as gold, silver, copper, silver-plated copper powder, silver-copper composite powder, silver-copper alloy, amorphous copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, malbutene, and platinum, inorganic powders coated with these metals, powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, and ruthenium oxide, inorganic powders coated with these metal oxides, carbon nanotubes, carbon black, and graphite.

[0021] Examples of organic pigments include various pigments used in inks, etc. Examples of such pigments include soluble azo pigments, insoluble azo pigments, phthalocyanine pigments, quinacridone pigments, isoindolinone pigments, isoindoline pigments, perylene pigments, perinone pigments, dioxazine pigments, anthraquinone pigments, dianthraquinonyl pigments, anthrapyrimidine pigments, anthanthrone pigments, indanthrone pigments, flavanthrone pigments, pyranthrone pigments, diketopyrrolopyrrole pigments, and the like.

[0022] The resin composition of the present invention has a resistivity of 5,000 Ω·cm or more and 25,000 Ω·cm or less when the nonvolatile content is adjusted to 8 mass % with N-methyl-2-pyrrolidone. Such a resin composition can achieve both good dispersibility and good electrode characteristics. In addition, the resistivity can be measured by first measuring the nonvolatile content of the resin composition, adding N-methyl-2-pyrrolidone so that the nonvolatile content is 8 mass%, and mixing to prepare a sample for measuring liquid resistivity. The resistivity can be measured by the method described in the Examples.

[0023] From the viewpoint of achieving both the dispersibility of the dispersed material and the electrode resistance, the resistivity is preferably from 5,000 Ω·cm to 20,000 Ω·cm, and more preferably from 7,000 Ω·cm to 15,000 Ω·cm. The resistivity of the resin composition can be adjusted by controlling the molecular weight, molecular weight distribution, ion concentration, etc. of the copolymer by modifying the copolymer with a basic compound such as an alkali metal compound, or by applying a shear stress to the copolymer. In this specification, modification of a copolymer includes not only modification of a part of the structural units of the copolymer by hydrolysis or the like, but also changes in the viscoelasticity and molecular weight of the copolymer.

[0024] The initial viscosity of the resin composition of the present embodiment is preferably from 10 mPa·s to 2,000 mPa·s, and more preferably from 100 mPa·s to 2,000 mPa·s, as measured at 100 rpm and 25° C. using a Brookfield viscometer. If the viscosity is within the above range, the stability of the resin composition can be improved. Furthermore, in the case where the resin composition contains an alkali metal compound, precipitation of the alkali metal compound is suppressed, resulting in more excellent stability.

[0025] (Copolymer(X)) The copolymer (X) is a copolymer having an alkylene structural unit and a nitrile group-containing structural unit, and may have other structural units.

[0026] From the viewpoint of dispersibility of the dispersed material, the total content of the alkylene structural units and the nitrile group-containing structural units is preferably 50% by mass or more and 100% by mass or less, and more preferably 80% by mass or more, based on 100% by mass of the copolymer (X). When the copolymer (X) is a modified copolymer, from the viewpoint of dispersibility of the dispersed material, the total content of the alkylene structural unit and the nitrile group-containing structural unit is preferably 50% by mass or more and 100% by mass or less, based on 100% by mass of the copolymer (X). When the nitrile group-containing structural unit is modified by hydrolysis, the total content is preferably 50% by mass or more and 97% by mass or less, more preferably 80% by mass or more and 95% by mass or less. The content of other structural units is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. When the nitrile group-containing structural unit has a modified amide group-containing structural unit, the content of the amide group-containing structural unit is preferably 5% by mass or less, more preferably 3% by mass or less, based on 100% by mass of the copolymer (X). If the content of the amide group-containing structural unit is large, when the copolymer is dissolved in the electrolyte, the viscosity of the electrolyte increases, and the ion conductivity may be significantly reduced.

[0027] The copolymer (X) is preferably modified by adjusting the amount of a basic compound such as an alkali metal compound added to control only the molecular weight or properties such as viscoelasticity while maintaining the composition.

[0028] A structural unit is a state in which a monomer is incorporated into a polymer after polymerization, and the content of a structural unit formed by polymerizing a monomer usually coincides with the ratio of the monomer to the total monomers used in the polymerization of the polymer (feed ratio), unless otherwise specified. In other words, the content of each monomer based on the total of all monomers is the content of each structural unit.

[0029] The copolymer (X) may be a copolymer modified by adding a basic compound such as an alkali metal compound. When the nitrile group contained in the nitrile group-containing structural unit of the copolymer is modified by hydrolysis or the like, it is preferable that the content of the alkylene structural unit and the nitrile group-containing structural unit of the copolymer (X) after modification is within the above range. The content of the alkylene structural unit and the nitrile group-containing structural unit can be calculated by IR measurement. For example, it can be calculated by the method described in ISO14558:2016. It can also be measured by the ATR method without using the KBr tablet method. By using the above method, the structural unit and its content can be identified even for the copolymer (X) modified with a basic compound.

[0030] The number average molecular weight (Mn) of the copolymer (X) of the present embodiment is preferably 70,000 or less, more preferably 50,000 or less, and even more preferably 30,000 or less. Also, it is preferably 10,000 or more. When the number average molecular weight (Mn) of the copolymer (X) is within the above range, the copolymer is easily adsorbed to the dispersed material, and the dispersed material is easily wetted by the solvent.

[0031] The weight average molecular weight (Mw) of the copolymer (X) of this embodiment is preferably 20,000 or more and 180,000 or less, more preferably 20,000 or more and 150,000 or less, and even more preferably 20,000 or more and 100,000 or less.

[0032] The Z-average molecular weight (Mz) of the copolymer (X) of this embodiment is preferably 20,000 or more and 250,000 or less, more preferably 20,000 or more and 200,000 or less, even more preferably 25,000 or more and 180,000 or less, and particularly preferably 30,000 or more and 100,000 or less.

[0033] When the weight-average molecular weight (Mw) and Z-average molecular weight (Mz) of the copolymer (X) are within the above ranges, not only is dispersion of a dispersed material such as a carbon material easy to proceed, but the viscosity of the resin composition is also low, which further improves the efficiency of removing metal foreign particles contained in the resin composition with a filter or magnet. The number average molecular weight (Mn), weight average molecular weight (Mw), and Z average molecular weight (Mz) are values ​​calculated in terms of polystyrene and can be measured by gel permeation chromatography (GPC).

[0034] The Z-average molecular weight is a weighted average using the square of the molecular weight as the weight, and is a value that is easily influenced by the high molecular weight. The copolymer (X) has a molecular weight distribution, and the low molecular weight component functions to improve the wettability of the dispersed material. In addition, the high molecular weight component functions to improve the viscosity stability of the dispersed material, the oxidation resistance of the copolymer, the resistance to dissolution in the electrolyte, and other battery properties. By controlling the Z-average molecular weight of the copolymer (X) to fall within the above range before adding a dispersed material such as a carbon material to the resin composition, the viscosity of the resin composition can be reduced, and the dispersed material can be easily wetted, facilitating the progress of dispersion. In addition, since the viscosity of the carbon material dispersion composition described later is low, when a dispersing machine using media such as a bead mill is used, the dispersion media moves well. Since the kinetic energy of the dispersion media is proportional to the mass and the square of the speed of the dispersion media, by efficiently moving the dispersion media in the carbon material dispersion composition, not only can the desired degree of dispersion be adjusted, but the carbon material dispersion composition is homogenized, and a carbon material dispersion composition having excellent temporal stability and electrical conductivity can be obtained.

[0035] The Z-average molecular weight (Mz) of the copolymer (X) can be controlled by the synthesis conditions of the copolymer (X) (composition, amount of the copolymer, catalyst, reaction temperature, reaction time, etc.), modifying the copolymer, applying shear stress to the copolymer, etc. The Z-average molecular weight can be reduced by applying mechanical shear stress using, for example, a roll or a kneader.

[0036] The polydispersity index (Mw / Mn) of the copolymer (X) of the present embodiment is preferably 2.2 or less, more preferably 2.0 or less, and even more preferably 1.8 or less, and is preferably 1.2 or more. When the polydispersity index (Mw / Mn) is within the above range, the ratio of the low molecular weight component contained in the copolymer (X) is appropriate, and in particular, when dispersing a carbon material, the dispersed material is quickly wetted, so that dispersion easily proceeds, and a carbon material dispersion composition can be obtained while maintaining the structure of the carbon material, and an electrode film or secondary battery having high electrical conductivity and adhesion can be easily obtained.

[0037] The ratio (Mz / Mw) of the weight average molecular weight (Mw) to the Z average molecular weight (Mz) of the copolymer (X) is preferably 2.2 or less, more preferably 2.0 or less, even more preferably 1.9 or less, and particularly preferably 1.8 or less. Also, it is preferably 1.5 or more, more preferably 1.6 or more. When the ratio (Mz / Mw) of the weight average molecular weight (Mw) to the Z average molecular weight (Mz) is within the above range, the ratio of the high molecular weight component contained in the copolymer (X) is appropriate, and a dispersion composition having good dispersion stability of the dispersed material is easily obtained.

[0038] The number average molecular weight (Mn), weight average molecular weight (Mw), and Z average molecular weight (Mz) of the copolymer (X) can be adjusted, for example, by dispersing the copolymer and an amide-based polar solvent under high pressure. A resin composition containing an amide-based polar solvent may be dispersed under high pressure. For high pressure dispersion, "Starburst" manufactured by Sugino Machine Ltd. can be used. In particular, the number average molecular weight (Mn) is preferably adjusted by dispersing the copolymer and an amide-based polar solvent under high pressure in the presence of an alkali metal.

[0039] [Alkylene structural unit] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure. However, this does not include structural units having a nitrile group.

[0040] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1A).

[0041] General formula (1A) [ka]

[0042] In general formula (1A), n represents an integer of 1 or more. n is preferably an integer of 2 or more, and more preferably an integer of 3 or more. n is preferably an integer of 5 or less, and more preferably an integer of 4 or less. In particular, n is preferably 3.

[0043] The alkylene structural unit preferably contains a structural unit represented by the following general formula (1B).

[0044] General formula (1B) [ka]

[0045] In general formula (1B), n represents an integer of 1 or more. n is preferably an integer of 4 or less, more preferably an integer of 3 or less, and even more preferably an integer of 2 or less. In particular, n is preferably 2.

[0046] The method for introducing an alkylene structural unit into the copolymer is not particularly limited, but examples thereof include the following method (1a) or (1b).

[0047] In the method (1a), a copolymer is prepared by polymerization reaction using a monomer composition containing a conjugated diene monomer. The prepared copolymer contains monomer units derived from the conjugated diene monomer. In the present invention, the "monomer units derived from the conjugated diene monomer" may be referred to as "conjugated diene monomer units", and the same may be omitted for monomer units derived from other monomers. Next, the conjugated diene monomer units are hydrogenated to convert at least a part of the conjugated diene monomer units into alkylene structural units. Hereinafter, "hydrogenation" may be referred to as "hydrogenation". The finally obtained copolymer contains units obtained by hydrogenating the conjugated diene monomer units as alkylene structural units.

[0048] The conjugated diene monomer unit includes at least a monomer unit having one carbon-carbon double bond. For example, the 1,3-butadiene monomer unit, which is a conjugated diene monomer unit, includes at least one monomer unit selected from the group consisting of a monomer unit having a cis-1,4 structure, a monomer unit having a trans-1,4 structure, and a monomer unit having a 1,2 structure, and may include two or more monomer units. The conjugated diene monomer unit may further include a monomer unit having no carbon-carbon double bond and including a branch point. In this specification, the "branch point" refers to a branch point in a branched polymer, and when the conjugated diene monomer unit includes a monomer unit having a branch point, the above-prepared copolymer and the copolymer are branched polymers.

[0049] In the method (1b), a copolymer is prepared by polymerization reaction using a monomer composition containing an α-olefin monomer. The prepared copolymer contains α-olefin monomer units. The finally obtained copolymer contains the α-olefin monomer units as alkylene structural units.

[0050] Among these, the method (1a) is preferred because the copolymer can be easily produced. The carbon number of the conjugated diene monomer is 4 or more, preferably 4 to 6. Examples of the conjugated diene monomer include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among these, 1,3-butadiene is preferred. The alkylene structural unit preferably contains a structural unit (hydrogenated conjugated diene monomer unit) obtained by hydrogenating a conjugated diene monomer unit, and more preferably contains a structural unit (hydrogenated 1,3-butadiene monomer unit) obtained by hydrogenating a 1,3-butadiene monomer unit. The conjugated diene monomer can be used alone or in combination of two or more kinds.

[0051] The hydrogenation is preferably a method capable of selectively hydrogenating conjugated diene monomer units. Examples of the hydrogenation method include known methods such as oil phase hydrogenation and aqueous phase hydrogenation.

[0052] The hydrogenation can be carried out by a conventional method. For example, the hydrogenation can be carried out by treating a copolymer having conjugated diene monomer units dissolved in a suitable solvent with hydrogen gas in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include nickel, palladium, rhodium, platinum, and copper.

[0053] In the method (1b), the carbon number of the α-olefin monomer is 2 or more, preferably 3 or more, and more preferably 4 or more. The carbon number of the α-olefin monomer is preferably 6 or less, and more preferably 5 or less. Examples of the α-olefin monomer include α-olefin compounds such as ethylene, propylene, 1-butene, and 1-hexene. The α-olefin monomer may be used alone or in combination of two or more.

[0054] The alkylene structural unit preferably includes at least one selected from the group consisting of structural units containing a linear alkylene structure and structural units containing a branched alkylene structure, more preferably includes at least one selected from the group consisting of structural units consisting only of linear alkylene structures and structural units consisting only of branched alkylene structures, and further preferably includes at least one selected from the group consisting of structural units represented by the above formula (1A) and structural units represented by the above formula (1B).

[0055] The content of the alkylene structural unit is preferably 50% by mass or more and 75% by mass or less, more preferably 55% by mass or more and 70% by mass or less, and even more preferably 55% by mass or more and 65% by mass or less, based on 100% by mass of the total content of the alkylene structural unit and the nitrile group-containing structural unit. By setting the content of the alkylene structural unit within the above range, the adsorption to the dispersed material and the affinity to the dispersion medium can be controlled, and the dispersed material can be stably present in the dispersion medium. In addition, the affinity of the copolymer to the electrolyte can be controlled, and problems such as the copolymer dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte can be prevented.

[0056] [Nitrile group-containing structural unit] The nitrile group-containing structural unit is a structural unit containing a nitrile group, preferably a structural unit containing an alkylene structure substituted with a nitrile group, more preferably a structural unit consisting of only an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The nitrile group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a nitrile group. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one.

[0057] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (2A).

[0058] General formula (2A) [ka]

[0059] In formula (2A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.

[0060] The nitrile group-containing structural unit may include a structural unit represented by the following general formula (2B).

[0061] General formula (2B) [ka]

[0062] In general formula (2B), R represents a methyl group.

[0063] The method of introducing the nitrile group-containing structural unit into the copolymer is not particularly limited, but a method of preparing a copolymer by polymerization reaction using a monomer composition containing a nitrile group-containing monomer (method (2a)) can be preferably used. The finally obtained copolymer contains the nitrile group-containing structural unit as a nitrile group-containing structural unit. Examples of the nitrile group-containing monomer that can form the nitrile group-containing structural unit include monomers containing a polymerizable carbon-carbon double bond and a nitrile group. For example, an α,β-ethylenically unsaturated group-containing compound having a nitrile group can be mentioned, and specifically, acrylonitrile, methacrylonitrile, etc. can be mentioned. In particular, from the viewpoint of increasing the intermolecular force between the copolymers and / or between the copolymer and the dispersed substance (adsorbed substance), it is preferable that the nitrile group-containing monomer contains acrylonitrile. The nitrile group-containing monomer can be used alone or in combination of two or more kinds.

[0064] The content of the nitrile group-containing structural unit is preferably 25% by mass or more and 50% by mass or less, more preferably 30% by mass or more and 45% by mass or less, and even more preferably 35% by mass or more and 45% by mass or less, based on 100% by mass of the total content of the alkylene structural unit and the nitrile group-containing structural unit. By setting the content of the nitrile group-containing structural unit within the above range, the adsorption to the dispersed material and the affinity to the dispersion medium can be controlled, and the dispersed material can be stably present in the dispersion medium. In addition, the affinity of the resin composition to the electrolyte can be controlled, and problems such as the resin composition dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte can be prevented.

[0065] [Other structural units] As long as the effects of the present invention are not impaired, structural units other than the alkylene structural unit and the nitrile group-containing structural unit may be contained as necessary. Examples of the other structural units include an amide group-containing structural unit and a carboxyl group-containing structural unit.

[0066] (alkali metals) The resin composition of the present invention contains an alkali metal. The content of the alkali metal in the resin composition is 50 ppm or more and less than 10,000 ppm. The concentration is preferably 500 ppm or more and 8000 ppm or less, and more preferably 2000 ppm or more and 5000 ppm or less. By ensuring that the content of the alkali metal is within the above range, when a dispersed material such as a carbon material is dispersed, the adsorptivity to non-dispersed materials and affinity to the dispersion medium are improved, thereby improving dispersibility. Furthermore, when the amount of alkali metal in the resin composition is within the above range, it becomes easy to control the molecular weight of the copolymer (X) within an appropriate range by modifying the copolymer with an alkali metal compound as a basic compound or by applying a shear stress to the copolymer, and this has the effect of improving the dispersibility of the dispersed material.

[0067] The alkali metal is contained in the resin composition by, for example, the monomer used to synthesize the copolymer before modification or the copolymer (X), the alkali metal compound used to modify the copolymer, the alkali metal compound used as an additive for adjusting pH, or the alkali metal contained in a solvent or the like. That is, the alkali metal contained in the resin composition includes not only alkali metal compounds intentionally added, but also alkali metals derived from the raw material monomers, catalysts, additives, solvents, and the like.

[0068] Examples of alkali metals include elements such as lithium, sodium, and potassium. The alkali metal content in the resin composition can be determined using an ICP emission spectrometer by the method described in the Examples.

[0069] (solvent) The resin composition of the present embodiment preferably contains a solvent. The solvent may be any solvent capable of dissolving the copolymer, and is preferably an amide-based polar solvent. Examples of the amide-based polar solvent include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, and N-methylcaprolactam. Among these, it is more preferable to contain at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.

[0070] (Method of producing resin composition) The method for producing the resin composition of the present embodiment is not particularly limited, and the resin composition may be produced by any method. For example, a method can be mentioned in which a copolymer is prepared by polymerization using a monomer composition containing a conjugated diene monomer and a nitrile group-containing monomer, and the conjugated diene monomer unit of the copolymer is hydrogenated to obtain a resin composition containing copolymer (X). Also, a resin composition containing copolymer (X) can be obtained by modifying a copolymer having an alkylene structural unit and a nitrile group-containing structural unit with a basic compound such as an alkyl metal compound or applying a shear stress to the copolymer.

[0071] Furthermore, as a method for making the alkali metal content 50 ppm or more and less than 10,000 ppm and the resistivity of the resin composition when the non-volatile content is adjusted to 8 mass% with N-methyl-2-pyrrolidone to 5,000 Ω cm or more and 25,000 Ω cm or less, in addition to the raw materials or blending amounts, etc. for producing the present copolymer, the following method can be mentioned. For example, <1> A method of applying shear stress to a copolymer containing an alkali metal using a grinder or the like; <2> A method in which an alkali metal or an alkali metal compound is added to a copolymer to obtain a modified copolymer, and a shear stress is applied to the modified copolymer using the above-mentioned pulverizer; <3> For example, a method in which a shear stress is applied to the copolymer using a pulverizer or the like, and then an alkali metal or an alkali metal compound is added thereto, can be mentioned. Among them, <2> or <3> The above method is preferred, and it is particularly preferred to use an alkali metal compound having a maximum particle size of 150 μm or less, particularly sodium hydroxide. By applying a shear stress to the copolymer in the presence of an alkali metal compound having a maximum particle size of 150 μm or less, the finely dispersed alkali metal compound absorbs moisture, comes into contact with the copolymer, and promotes the hydrolysis reaction of the copolymer, thereby making it possible to control the structure, molecular weight, and molecular weight distribution suitable for dispersing the material to be dispersed.

[0072] <2> or <3> In the above, the alkali metal compound used to modify the copolymer may be, for example, an alkali metal hydroxide or alkoxide, etc. Preferably, it is an alkali metal hydroxide.

[0073] That is, the method for producing a resin composition preferably includes, for example, a step of mixing an alkali metal compound with a copolymer having an alkylene structural unit and a nitrile group-containing structural unit to produce a resin composition containing copolymer (X) and an alkali metal.

[0074] In this case, the copolymer before modification is preferably a copolymer having alkylene structural units and nitrile group-containing structural units with a content of 50% by mass or more and 75% by mass or less of alkylene structural units and 25% by mass or more and 50% by mass or less of nitrile group-containing structural units, which is obtained by mixing an alkali metal compound with a copolymer having alkylene structural units and nitrile group-containing structural units.

[0075] In order to obtain a resin composition that satisfies the above requirements, the copolymer before modification is preferably dissolved in an amide polar solvent at 60° C. to 100° C. The alkali metal compound is preferably mixed at a temperature of 40° C. to 100° C., more preferably at 60° C. to 80° C.

[0076] The alkali metal compound may be an alkali metal hydroxide or an alkali metal alkoxide, and it is preferable to use an alkali metal hydroxide. Examples of the alkali metal hydroxide that can be used include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. From the viewpoints of processability such as particle size control and handling, sodium hydroxide is preferred because it has excellent dispersion stability of the dispersed material. Sodium hydroxide is hygroscopic and can exert an excellent effect when part of the structural units of the copolymer is modified by hydrolysis or the like. As the alkali metal alkoxide, for example, sodium ethoxide, sodium butoxide, etc. can be used.

[0077] The alkali metal compound used to modify the copolymer preferably has a maximum particle size of 150 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less, and preferably 20 μm or more. When the maximum particle size of the alkali metal compound is within the above range, the precipitation of the alkali metal compound in the resin composition is suppressed, and the stability of the resin composition is more excellent. The settling rate of the alkali metal compound in the resin composition can be estimated by Stokes' equation, and the viscosity of the resin composition and the density and particle size of the alkali metal compound are important in controlling the dispersion stability of the dispersed material. The maximum particle size of the alkali metal compound can be calculated, for example, by filtering through a filter with a known mesh size.

[0078] The particle size of the alkali metal compound is preferably controlled by dry and / or wet pulverization using a conventionally known pulverizer. By setting the maximum particle size of the alkali metal compound within the above range, it is possible to appropriately control not only the composition and structure of the structural units constituting the copolymer (X) but also the change in the molecular weight of the copolymer (X) due to modification. By controlling the molecular weight and molecular weight distribution of the copolymer (X) in this way, it is possible to obtain a dispersion composition with a lower viscosity when the dispersed material is dispersed. If the maximum particle size of the alkali metal compound is large, the alkali metal compound may precipitate in the resin composition, making it impossible to control the molecular weight of the copolymer, and may also reduce the stability over time of the carbon material dispersion composition and composite slurry described below.

[0079] A pulverizer is a device that applies forces such as compression, impact, shear, and friction to a sample to reduce its size. Devices that can be used to control particle size include mortars, pin mills, hammer mills, pulverizers, attritors, jet mills, cutter mills, ball mills, bead mills, colloid mills, conical mills, disk mills, edge mills, wonder crushers, vibration mills, ultrasonic homogenizers, and high-shear mixers.

[0080] <Carbon material dispersion composition> The carbon material dispersion composition of the present embodiment contains at least a carbon material and the resin composition of the present embodiment. It is preferable that the carbon material dispersion composition further contains a solvent. By containing a solvent in the carbon material dispersion composition, it is easy to obtain a carbon material dispersion composition having a good dispersion state.

[0081] (Carbon materials) As the carbon material, various carbon blacks such as acetylene black, furnace black, hollow carbon black, channel black, thermal black, and ketjen black can be used. In addition, amorphous carbonaceous materials such as oxidation-treated carbon black, graphitized carbon black, and mesophase carbon black, soft carbon, and hard carbon, carbon nanotubes or carbon nanofibers, which are fibrous carbon, and carbon fibers such as vapor-grown carbon fibers can also be used. Among them, it is preferable to include at least one selected from the group consisting of carbon black and carbon fiber, and it is particularly preferable to include carbon nanotubes.

[0082] The carbon purity of the carbon material is preferably 95% by mass or more, and more preferably 97% by mass or more, based on the mass of the carbon material (the mass of the carbon material being 100% by mass).

[0083] Carbon nanotubes have a structure in which planar graphite is wound into a cylindrical shape, and include single-walled carbon nanotubes and multi-walled carbon nanotubes, and these may be mixed. Among them, it is preferable to include multi-walled carbon nanotubes. Multi-walled carbon nanotubes have a structure in which two or more layers of graphite are wound, and single-walled carbon nanotubes have a structure in which one layer of graphite is wound. The sidewall of the carbon nanotube does not have to have a graphite structure. For example, carbon nanotubes with sidewalls having an amorphous structure can also be used as the carbon material.

[0084] The average outer diameter of the carbon nanotubes is preferably 1 nm to 25 nm, more preferably 3 nm to 20 nm, and even more preferably 4 nm to 15 nm. When the average outer diameter is within the above range, a good conductive network is easily formed in the electrode, and the active material inside the secondary battery is used uniformly during charging and discharging, so that deterioration of the active material is suppressed and the cycle characteristics of the secondary battery are further improved.

[0085] The BET specific surface area of ​​carbon nanotubes is 100m 2 / g or more 1000m 2 / g or less, and 2 / g or more 700m 2 / g or less is more preferable. When the BET specific surface area is within the above range, an efficient conductive network can be formed with a small amount, and the amount of conductive material in the electrode can be reduced. This increases the degree of freedom in battery design, such as increasing the amount of active material and binder resin. Furthermore, when preparing the composite slurry, the active material and the carbon nanotubes are more likely to be combined, making it easier to obtain an electrode film having a homogeneous conductive network in which the active material surface is coated with carbon nanotubes, which suppresses the electrolyte decomposition reaction at the interface between the electrolyte and the active material, thereby improving the cycle characteristics of the battery. The BET specific surface area can be measured by the BET method described in JIS Z 8830.

[0086] The G / D ratio (peak ratio of the G-band to the D-band) of carbon nanotubes is 1560 cm -1 ~1600cm -1 The maximum peak intensity in the range of G, 1310 cm -1 ~1350cm -1 When the maximum peak intensity within this range is D, the G / D ratio is preferably 0.5 to 10, and more preferably 0.7 to 4.5. When the G / D ratio of the carbon nanotubes is within the above range, it is believed that the contact resistance between the carbon nanotubes is small, and good electrical conductivity is easily obtained. It is also believed that the amount of functional groups on the multi-walled carbon nanotube surface is appropriate, and the affinity with the solvent is good, resulting in better dispersibility.

[0087] The volume resistivity of carbon nanotubes is 1.0×10 -2 Ω cm~3.0×10 -2 Ω cm is preferred, and 1.0×10 -2 Ω cm~2.0×10 -2 It is more preferable that the resistance is Ω·cm. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (Loresta GP Powder Resistivity Measuring System MCP-PD-51, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). When the volume resistivity is within the above range, the conductivity of the electrode film is likely to be good, and a secondary battery having excellent rate characteristics and cycle characteristics is likely to be obtained.

[0088] It is preferable that the carbon nanotubes have been removed of metallic foreign matter particles by magnetic force using an electromagnet. For example, it is preferable to remove metallic foreign matter particles by passing the carbon nanotubes through an electromagnet in the crushing process or filling process of the carbon nanotubes. The higher the carbon purity of the carbon nanotubes, the more preferable. The carbon purity is preferably 98.0 mass % or more, more preferably 99.5 mass % or more, even more preferably 99.8 mass % or more, and particularly preferably 99.9 mass % or more, based on 100 mass % of the carbon nanotubes. That is, the lower the content of metallic foreign particles, the better; it is preferably 2.0 mass % or less, more preferably 0.5 mass % or less, even more preferably 0.2 mass % or less, and particularly preferably 0.1 mass % or less, based on 100 mass % of the carbon nanotubes. By using carbon nanotubes produced by a method that does not use a metal catalyst as a nucleus, or carbon nanotubes obtained by a conventional purification method such as acid treatment, the content of metal foreign particles can be reduced to 0.5 mass% or less relative to 100 mass% of carbon nanotubes, thereby reducing the content of metal foreign particles in the carbon nanotube dispersion composition and improving the characteristics of secondary batteries. The carbon purity of the carbon nanotubes can be determined using an ICP emission spectrometer by the method described in the Examples.

[0089] The solvent is not particularly limited as long as it is miscible with the resin composition of the present embodiment, but it is preferable that the solvent can dissolve the resin composition, and is more preferable that the solvent is a high dielectric constant solvent, and preferably contains a solvent consisting of one type of high dielectric constant solvent or a mixed solvent consisting of two or more types of high dielectric constant solvents. In addition, the high dielectric constant solvent may be used by mixing one or more other solvents.

[0090] Examples of high dielectric constant solvents that can be used include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), and others, such as tetrahydrofuran, urea, and acetonitrile. The dispersion medium preferably contains an amide-based polar solvent, more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The relative dielectric constant of the high dielectric constant solvent can be a value described in the Solvent Handbook, etc., and is preferably 2.5 or more at 20°C. By using a high dielectric constant solvent, the interaction between the nitrile group contained in the resin composition of the present embodiment, the carbon material, and the solvent can be enhanced.

[0091] The water content of the solvent is preferably 100 ppm or more and 1500 ppm or less, and more preferably 100 ppm or more and 1000 ppm or less. When the water content is within the above range, the alkali metal contained in the resin composition of the present embodiment dissolves in the carbon material dispersion composition, and the dispersion stability of the carbon material dispersion composition tends to be good.

[0092] The content of the solvent in this embodiment is preferably 90% by mass to 99% by mass, and more preferably 92% by mass to 98% by mass, based on the mass of the carbon material dispersion composition (the mass of the carbon material dispersion composition being 100% by mass). When it is within the above range, a carbon material dispersion composition having flowability and excellent dispersion stability is easily obtained. By using a carbon material dispersion composition having excellent dispersion stability, an electrode film having stable conductivity is obtained, and the quality of a secondary battery is easily stabilized.

[0093] In order to obtain the carbon material dispersion composition of the present embodiment, it is preferable to carry out a treatment for dispersing the carbon material in a solvent. The dispersing device used for carrying out such a treatment is not particularly limited.

[0094] As the dispersing device, a dispersing machine that is generally used for dispersing pigments, etc., can be used. For example, a mixer such as a disperser, a homomixer, or a planetary mixer, a homogenizer (Advanced Digital Sonifer (registered trademark), MODEL 1 manufactured by BRANSON, Examples of media-type dispersers include 450DA, M-Technique's "Clearmix," PRIMIX's "Filmix," Silverson's "Abramix," etc.), paint conditioners (Red Devil), colloid mills (PUC's "PUC Colloid Mill," IKA's "Colloid Mill MK"), cone mills (IKA's "Cone Mill MKO," etc.), ball mills, sand mills (Shinmaru Enterprises' "Dyno Mill," etc.), attritors, pearl mills (Eirich's "DCP Mill," etc.), and Coball mills; high-pressure homogenizers (Genus' "Genus PY," Sugino Machine's "Starburst," Nanomizer's "Nanomizer," etc.); media-less dispersers such as M-Technique's "Clear SS-5" and Nara Kikai's "MICROS," and other roll mills, but are not limited to these.

[0095] The content of the carbon material contained in the carbon material dispersion composition is preferably 1 mass% or more and 20 mass% or less, more preferably 2 mass% or more and 15 mass% or less, and even more preferably 3 mass% or more and 10 mass% or less, based on the mass of the carbon material dispersion composition (the mass of the carbon material dispersion composition being 100 mass%).

[0096] The content of the dispersant contained in the carbon material dispersion composition is preferably 5% by mass or more and 100% by mass or less, more preferably 10% by mass or more and 75% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less, based on the mass of the carbon material (the mass of the carbon material being 100% by mass). When the amount of the dispersant is within the above range, the dispersion stability of the carbon material in the carbon material dispersion composition tends to be good. In addition, the peel strength of the electrode for the secondary battery is good.

[0097] The carbon material dispersion composition has a water content of preferably 100 ppm to 1500 ppm, more preferably 200 ppm to 1000 ppm. When the water content of the carbon material dispersion composition is within the above range, gelation of the composite slurry described below is suppressed, and a composite slurry and an electrode film of stable quality are likely to be obtained.

[0098] The initial viscosity of the carbon material dispersion composition of this embodiment, measured using a Brookfield viscometer at 25° C. and 100 rpm, is preferably 100 mPa·s to 2,000 mPa·s, and more preferably 200 mPa·s to 1,000 mPa·s. When the initial viscosity of the carbon material dispersion composition is within the above range, it is considered that the dispersion state of the carbon material contained in the carbon material dispersion composition is appropriate, and a conductive network is easily formed.

[0099] The viscosity of the carbon material dispersion composition of this embodiment after storage for one week at 60°C, as measured after cooling to 25°C with a B-type viscometer at 25°C and a rotor rotation speed of 100 rpm, is preferably 500 mPa·s or more and 6,000 mPa·s or less, more preferably 500 mPa·s or more and 3,000 mPa·s or less, and even more preferably 500 mPa·s or more and 2,000 mPa·s or less.

[0100] A carbon material dispersion composition having a viscosity within the above range is considered to have an appropriate composition ratio of the carbon material, the resin composition, and the solvent, and a suitable dispersion process, and therefore has good dispersion stability. Since the adsorption reaction of the resin composition contained in the carbon material dispersion composition onto the surface of the carbon material is an endothermic reaction, a necessary and sufficient amount of the resin composition can be determined to obtain a carbon material dispersion composition having excellent dispersion stability by evaluating the viscosity of the carbon material dispersion composition after storage under high temperature conditions.

[0101] The carbon material dispersion composition of the present embodiment is preferably used after removing metallic foreign matter with a filter or a magnet.

[0102] [Process for removing metal foreign particles] The method for removing the metal foreign particles is not particularly limited, but examples thereof include a filtration step in which the particles are filtered out using a filter, and a magnetic separation step such as a magnetic separation treatment using an electromagnet. It is preferable to include a filtration step and a magnetic separation step, because the magnetic separation step makes it possible to remove metallic foreign particles contained in the carbon material, and the filtration step makes it possible to recover metallic foreign particles that cannot be removed by a magnet. It is more preferable to carry out the magnetic separation step after the filtration step. By carrying out the filtration step as the final step before shipping the carbon material dispersion composition, metal foreign particles from piping and the like can also be removed.

[0103] (Magnetic selection process) As a method for removing metal foreign particles by using a magnetic force in the magnetic separation step, various conventionally known methods can be used. For example, a method for removing metal foreign particles by passing a carbon material dispersion composition through an electromagnet during the production step of the carbon material dispersion composition is preferred.

[0104] The magnetic flux density of the electromagnet is preferably from 5,000 to 20,000 gauss, more preferably from 10,000 to 20,000 gauss. By using an electromagnet in the above range, not only can the metal foreign particles contained in the carbon material be removed, but also the metal foreign particles generated during the manufacturing process can be removed.

[0105] Specifically, for example, CS-150HHH, CS-250HHH, CS-300HHH manufactured by Nippon Magnetics Co., Ltd., DVF-50-6, DVF-50-9, DVF-50-12 manufactured by Nippon Eriez Magnetics Co., Ltd., EMF-100S, EMF-150S, EMF-250S, EMF-300S manufactured by Taiho Magnetic Co., Ltd., and the like can be used.

[0106] The flow rate of the carbon material dispersion composition when it comes into contact with the electromagnet is preferably 1 L / min or more and 300 L / min or less, and more preferably 30 L / min or more and 200 L / min or less.

[0107] The carbon material dispersion composition is preferably passed through the electromagnet three or more times. If the number of passes is small, there is a possibility that metal foreign particles cannot be removed. When passing through the electromagnet in a circulating manner, it is preferable to pass through the electromagnet more times in consideration of the uniformity inside the tank used in the manufacturing process.

[0108] (filtration process) The filter for filtering out the foreign metal particles may be a surface filter such as a membrane filter or a depth filter, but a depth filter is more preferable. Since foreign metal particles are not spherical and often have an orientation, the use of a depth filter can efficiently remove the foreign metal particles from the carbon material dispersion composition.

[0109] Unlike a surface filter (a filter that mainly captures particulate matter in a fluid on the filter surface), a depth filter is a filter that mainly captures particulate matter in a fluid inside the filter medium, and has the characteristics of having high particle retention performance and being less likely to clog. By using a depth filter, it is possible to more selectively remove metal foreign particles from a carbon material dispersion composition.

[0110] As the depth filter, for example, 3M(TM) PP nonwoven fabric depth cartridge NT-T series can be used.

[0111] The filtration accuracy of the filter is preferably 5 μm or more and 50 μm or less, and more preferably 10 μm or more and 40 μm or less. When a filter with a small pore size is used to increase the metal foreign particle removal rate in the carbon material dispersion composition, the removal efficiency of the metal foreign particle may decrease due to clogging of the carbon material. On the other hand, when the carbon material dispersion composition is filtered through a filter in the above range, the removal efficiency of the metal foreign particle is high when the filter is used, so that a carbon material dispersion composition with fewer metal foreign particles is easily obtained.

[0112] <Composition slurry> The composite slurry of the present embodiment contains a carbon material dispersion composition and an active material. That is, the composite slurry contains at least the resin composition of the present invention, a carbon material, an active material, and preferably further contains a binder resin.

[0113] The binder resin is a resin used to bond the carbon material. There is no particular limitation on the binder resin, but examples of the binder resin include polymers or copolymers containing fluororesin, ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid ester, methacrylic acid, methacrylic acid ester, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as structural units; polyurethane resin, polyester resin, phenol resin, epoxy resin, phenoxy resin, urea resin, melamine resin, alkyd resin, acrylic resin, formaldehyde resin, silicone resin, and fluororesin; cellulose resin such as carboxymethylcellulose; rubbers such as styrene butadiene rubber; and conductive resins such as polyaniline and polyacetylene. Among these, it is preferable to use a fluororesin as the binder resin from the viewpoint of electrochemical oxidation-reduction resistance.

[0114] As the fluororesin of this embodiment, for example, polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene are preferable.

[0115] The weight average molecular weight of the fluororesin is preferably from 10,000 to 2,000,000, more preferably from 100,000 to 1,000,000, and particularly preferably from 200,000 to 1,000,000.

[0116] An active material is a material that is the basis of a battery reaction. Active materials are divided into positive electrode active materials and negative electrode active materials based on their electromotive force. In this specification, positive electrode active materials and negative electrode active materials may be simply referred to as "active materials." Active materials are a material that is the basis of a battery reaction. Active materials are divided into positive electrode active materials and negative electrode active materials based on their electromotive force.

[0117] The positive electrode active material is not particularly limited, but may be a metal compound such as a metal oxide or metal sulfide capable of doping or intercalating lithium ions or sodium ions, or a conductive polymer. Examples of the positive electrode active material include oxides of transition metals such as Fe, Co, Ni, and Mn, composite oxides with lithium or sodium, inorganic compounds such as transition metal sulfides, polyanion compounds, and Prussian blue. Specific examples include MnO, VO, VO 13 , transition metal oxide powders such as TiO2, composite oxide powders of lithium and transition metals such as lithium nickel oxide, lithium cobalt oxide, lithium manganate, and lithium manganate with a spinel structure, lithium iron phosphate-based materials which are phosphate compounds with an olivine structure, transition metal sulfide powders such as TiS2 and FeS, sodium ferrate, sodium manganate, sodium chromate, and sodium nickelate with a layered structure, and sodium iron phosphate-based materials which are phosphate compounds with an olivine structure. Conductive polymers such as polyaniline, polyacetylene, polypyrrole, and polythiophene can also be used. The above inorganic compounds and organic compounds may also be used in combination.

[0118] The positive electrode active material is preferably a composite oxide of lithium containing a transition metal such as Al, Fe, Co, Ni, or Mn, more preferably a composite oxide of lithium containing any of Al, Co, Ni, or Mn, and particularly preferably a composite oxide of lithium containing Ni and / or Mn. When these active materials are used, particularly good effects can be obtained.

[0119] The negative electrode active material is not particularly limited as long as it can be doped or intercalated with lithium or sodium ions. For example, alloy systems such as metallic Li, its alloys such as tin alloys, silicon alloys, and lead alloys; metal oxide systems such as LiXFe2O3, LiXFe3O4, LiXWO2 (where x is a number between 0 < x < 1), lithium titanate, lithium vanadate, and lithium silicate; conductive polymer systems such as polyacetylene and poly-p-phenylene; amorphous carbonaceous materials such as soft carbon and hard carbon, artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, carbon black, mesophase carbon black, resin-fired carbon materials, gas-phase grown carbon fibers, and carbon fibers. These negative electrode active materials can be used alone or in combination of two or more.

[0120] The BET specific surface area of the active material is preferably 0.1 m 2 / g or more and 10 m 2 / g or less, more preferably 0.2 m 2 / g or more and 5 m 2 / g or less, and even more preferably 0.3 m 2 / g or more and 3 m 2 / g or less.

[0121] The average particle diameter of the active material is preferably in the range of 0.05 μm to 100 μm, and more preferably in the range of 0.1 μm to 50 μm. The average particle diameter of the active material as referred to in this specification is the average value of the particle diameters measured by an electron microscope for the active material.

[0122] To obtain the composite material slurry of this embodiment, it is preferable to add the active material to the carbon material dispersion composition and then perform a dispersion treatment. The dispersion device used for such treatment is not particularly limited. The composite material slurry can be obtained using the dispersion device described for the carbon material dispersion composition.

[0123] The content of the active material in the composite slurry is preferably 20% by mass to 85% by mass, and particularly preferably 40% by mass to 85% by mass, based on 100% by mass of the composite slurry.

[0124] The content of the carbon material in the composite slurry is preferably 0.05% by mass to 10% by mass, more preferably 0.1% by mass to 5% by mass, and even more preferably 0.1% by mass to 3% by mass, based on 100% by mass of the active material.

[0125] The content of the binder resin in the composite slurry is preferably 0.5% by mass to 20% by mass, more preferably 1% by mass to 10% by mass, and particularly preferably 1% by mass to 5% by mass, based on 100% by mass of the active material.

[0126] The solid content concentration of the composite slurry is preferably 30% by mass to 90% by mass, and more preferably 40% by mass to 85% by mass, based on 100% by mass of the composite slurry.

[0127] The water content in the composite slurry is preferably 500 ppm or less, more preferably 300 ppm or less, and particularly preferably 100 ppm or less.

[0128] ≪Electrode≫ The electrode film of this embodiment includes a current collector and an electrode film formed from a composite material slurry. The electrode film is a coating film of a composite material slurry, for example, a coating film formed by coating a composite material slurry on a current collector and drying the composite material slurry to form an electrode composite material layer.

[0129] The material and shape of the current collector used in the electrode film of this embodiment are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used.

[0130] The method of applying the composite slurry onto the current collector to form the electrode film is not particularly limited, and a known method can be used. Specifically, examples of the method include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. The drying method can be, but is not limited to, standing drying, a blower dryer, a hot air dryer, an infrared heater, or a far infrared heater.

[0131] After coating, the electrode mixture layer may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode mixture layer is generally 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0132] ≪Secondary battery≫ The secondary battery of this embodiment includes an electrode having the electrode film of the present invention and an electrolyte. The carbon material dispersion composition using the resin composition of this embodiment forms a good conductive network in the secondary battery electrode, so it has excellent rate characteristics, and the active material is used uniformly during charging and discharging, so that the active material is not easily deteriorated. Furthermore, overcharging and overdischarging during charging and discharging are suppressed. Therefore, deterioration of the battery characteristics due to electrolyte decomposition and metal precipitation is not easily caused, and the cycle characteristics are excellent.

[0133] The positive electrode can be prepared by coating a composite slurry containing a positive electrode active material on a current collector and drying the coated composite slurry to form an electrode film.

[0134] The negative electrode may be prepared by coating a composite slurry containing a negative electrode active material on a current collector and drying the coated composite slurry to form an electrode film.

[0135] As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto, and those containing sodium salts can also be used. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0136] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0137] The secondary battery of the present embodiment preferably includes a separator. Examples of the separator include, but are not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and those that have been subjected to a hydrophilic treatment.

[0138] The structure of the secondary battery of the present embodiment is not particularly limited, but is usually composed of a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.

[0139] The applications of the secondary battery of this embodiment are not particularly limited, and specifically, it can be used as a power source for consumer devices such as mobile phones, notebook computers, and digital cameras, an emergency power source for hospitals, factories, buildings, and the like, and for vehicles such as hybrid automobiles, plug-in hybrid automobiles, electric automobiles, power-assisted bicycles, and railroad cars. The secondary battery is, for example, used to recover regenerative energy for the motive power of a vehicle.

[0140] In particular, since the secondary battery has high charge / discharge performance and excellent cycle characteristics, it can be suitably used in vehicles, and a vehicle with high safety and improved fuel efficiency can be obtained. Furthermore, it can exert excellent effects in vehicle applications where charging and discharging at a large current is desired.

[0141] The mounting position of the secondary battery in the vehicle of this embodiment is not particularly limited. For example, when the secondary battery is mounted in an automobile, the secondary battery may be mounted in the engine compartment, the rear of the vehicle body, or in the seat. It can be mounted underneath. EXAMPLES

[0142] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not exceed the gist of the invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". The blending amounts in the tables are parts by mass. The blank spaces in the tables indicate that no blending was performed.

[0143] The materials used in the examples and comparative examples are shown below. Hydrogenated nitrile butadiene rubber (manufactured by Zannan Scitech, liquid hydrogenated nitrile butadiene rubber, number average molecular weight 20,000, weight average molecular weight 35,000, Z average molecular weight 60,000, alkylene structural units 66% by mass, nitrile group-containing structural unit content 34% by mass), hereinafter referred to as HNBR1. Hydrogenated nitrile butadiene rubber (Zannan Scitech, ZN35052, Mooney viscosity 20, number average molecular weight 48000, weight average molecular weight 110,000, Z average molecular weight 210,000, alkylene structural units 66% by mass, nitrile group-containing structural unit content 34% by mass), hereinafter referred to as HNBR2. Hydrogenated nitrile butadiene rubber (Zannan Scitech, ZN35053, Mooney viscosity 35, number average molecular weight 53000, weight average molecular weight 133,000, Z average molecular weight 270,000, alkylene structural units 64% by mass, content of nitrile group-containing structural units 36% by mass), hereinafter referred to as HNBR3. Hydrogenated nitrile butadiene rubber (Zannan Scitech, ZN35056, Mooney viscosity 65, number average molecular weight 75,000, weight average molecular weight 183,000, Z-average molecular weight 364,000, alkylene structural units 64% by mass, nitrile group-containing structural unit content 36% by mass), hereinafter referred to as HNBR4. Hydrogenated nitrile butadiene rubber (ARLANXEO, Therban(R) 3406, Mooney viscosity 63, number average molecular weight 78,000, weight average molecular weight 209,000, Z-average molecular weight 434,000, alkylene structural units 66% by mass, content of nitrile group-containing structural units 34% by mass), hereinafter referred to as HNBR5. Carbon nanotubes (JEIO, JENOTUBE6A, average outer diameter 6nm, BET specific surface area 650m 2 / g) hereinafter referred to as CNT1. Carbon nanotubes (JEIO, JENOTUBE10B, average outer diameter 10 nm, BET specific surface area 230 m 2 / g) hereinafter referred to as CNT2. HS-100: Denka Black HS-100 (manufactured by Denka Co., Ltd., acetylene black, average primary particle diameter 48 nm, BET specific surface area 39 m 2 / g) hereinafter referred to as CB1.

[0144] The methods for measuring the physical properties of the materials used in each of the examples and comparative examples are as follows.

[0145] <Specific surface area> The BET specific surface area of ​​carbon nanotubes and carbon black can be measured by the BET method using nitrogen adsorption measurement in accordance with JIS Z 8830.

[0146] <Average outer diameter> The average outer diameter of carbon nanotubes can be calculated by observing and photographing carbon nanotubes with a transmission electron microscope, then arbitrarily selecting 300 carbon nanotubes from the photograph obtained and measuring the outer diameter of each of them. The average primary particle diameter of carbon black can be calculated by first observing and photographing carbon black with a transmission electron microscope, then arbitrarily selecting 100 spherical carbon black primary particles from the photograph, and measuring the outer diameter of each of them.

[0147] <Mooney viscosity> The Mooney viscosity of the hydrogenated nitrile butadiene rubber was measured using an L-type rotor at a temperature of 100° C. (ML1+4, 100° C.) in accordance with Japanese Industrial Standard JIS K6300-1.

[0148] <Preparation of standard negative electrode> 0.5 parts by mass of acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka), 1 part by mass of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500L, manufactured by Nippon Paper Industries Co., Ltd., non-volatile content 100%), and 98.4 parts by mass of water were added to a plastic container with a capacity of 150 ml, and then the mixture was stirred for 30 seconds at 2000 rpm using a centrifugal mixer (Thinky Awatori Rentaro, ARE-310). Furthermore, 92 parts by mass of artificial graphite (Nippon Graphite Industry Co., Ltd., CGB-20) and 5 parts by mass of silicon oxide (Osaka Titanium Technology Co., Ltd., SILICON MONOOXIDE SiO 1.3C 5 μm, non-volatile content 100%) were added as active materials, and the mixture was stirred for 10 minutes at 3000 rpm using a high-speed stirrer. Next, 3.1 parts by mass of styrene butadiene rubber (SBR, TRD2001, manufactured by JSR Corporation) was added and stirred at 2000 rpm for 30 seconds using the centrifugal mixer to obtain a negative electrode composite slurry. Thereafter, the negative electrode composite slurry was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode became 8 mg / cm. 2 After coating on copper foil so that the thickness was 1.6g / cm, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, rolling was performed using a roll press (Thank Metal Co., Ltd., 3t hydraulic roll press) to reduce the density of the composite layer to 1.6g / cm. 3 A standard negative electrode was prepared.

[0149] <Preparation of alkali metal compound dispersion> Capacity 2000cm 3 950 parts by mass of NMP and 50 parts by mass of NaOH (sodium hydroxide, Tosoh Corporation, Toso Pearl) were added to a plastic container, and a fine emulsion screen was attached to a high-shear mixer (L5M-A, Silverson), and the mixture was dispersed at a speed of 9000 rpm until the entire mixture was uniform.Then, using a filtration bell, the mixture was passed through a nylon filter with 150 μm openings to produce a NaOH dispersion (NaOH concentration 5% by mass). The maximum extrusion of sodium hydroxide was below 150 μm.

[0150] <Physical property measurement and evaluation method> The methods for measuring and evaluating the physical properties of the resin compositions, carbon material dispersion compositions, electrode films, and secondary batteries used in the examples and comparative examples described later are as follows.

[0151] <Measurement of number average molecular weight, weight average molecular weight and Z average molecular weight of copolymer> (Preparation of sample for molecular weight measurement) To measure the number average molecular weight (Mn), weight average molecular weight (Mw) and Z average molecular weight (Mz) of the copolymer, a sample for molecular weight measurement was prepared by the following method. The resin composition was dropped into purified water to precipitate the copolymer, and the precipitate was collected by filtration using a Buchner funnel. The precipitate was rinsed by sprinkling purified water on the Buchner funnel as it was, and then dissolved in tetrahydrofuran (THF) to obtain a solution. The obtained solution was dropped again into purified water to carry out the filtration and washing steps using purified water, and the precipitate was redissolved in THF to obtain a sample for molecular weight measurement.

[0152] (Molecular Weight Measurement) Using a sample for molecular weight measurement, the measurement was performed by gel permeation chromatography (GPC) equipped with an RI detector. The apparatus used was HLC-8320GPC (manufactured by Tosoh Corporation), and three separation columns were connected in series. The packing materials used were "TSK-GEL SUPER AW-4000", "AW-3000", and "AW-2500" manufactured by Tosoh Corporation, respectively. The oven temperature was 40°C, and an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr was used as the eluent, and the measurement was performed at a flow rate of 0.6 mL / min. The concentration of the measurement sample was adjusted to 1% using a solvent consisting of the eluent, and 20 microliters were injected. The average molecular weight is a polystyrene equivalent value.

[0153] <Contents of alkylene structural units and nitrile group-containing structural units in the copolymer> (Preparation of sample for IR measurement) The resin composition was dropped into purified water to precipitate the copolymer, and the precipitate was collected by filtering through a Buchner funnel. The precipitate was rinsed directly on the Buchner funnel with purified water, and then dried at 140°C for 1 hour in a hot air oven to prepare a sample for IR measurement. (IR measurement) Using a sample for IR measurement, measurement was performed with a Fourier transform infrared spectrometer (Nicleti S5, manufactured by Thermo Fisher Scientific), and the contents of alkylene structural units and nitrile group-containing structural units of the copolymer in the resin composition were calculated.

[0154] <Measurement of Resistivity of Resin Composition> (Preparation of samples for resistivity measurement) Capacity 250cm 3 The resin composition and N-methyl-2-pyrrolidone were weighed out and placed in a plastic container to prepare 200 parts by mass of a sample for liquid resistivity measurement having a non-volatile content of 8% by mass. (Measurement of resistivity) The liquid resistance measurement sample was used to measure the resistance with a resistivity meter (IEST Battery Slurry Resistivity BSR2300, registered trademark), and the resistivity at 25° C. was calculated. The resistivity value was the measurement result of the middle channel.

[0155] <Measurement of alkali metal content in resin composition> The resin composition was dried using a hot air oven, and then decomposed with an acid using a microwave sample pretreatment device (Milestone General, ETHOS1) to calculate the alkali metals (lithium, sodium, potassium) contained in the resin composition. The content of the alkali metals was calculated as the sum of the contents of lithium, sodium, and potassium.

[0156] <Initial Viscosity of Carbon Material Dispersion Composition> The carbon material dispersion composition was left to stand in a thermostatic chamber at 25°C for at least one hour, and then immediately subjected to measurement using a Brookfield viscometer with a rotor rotation speed of 100 rpm. The initial viscosity was evaluated as follows: 100 mPa·s or more but less than 500 mPa·s: ◎ (excellent), 500 mPa·s or more but less than 1000 mPa·s: ◯ (good), 1000 mPa·s or more but less than 2000 mPa·s: △ (fair), and more than 2000 mPa·s: × (poor).

[0157] <Viscosity over time of carbon material dispersion composition> The carbon material dispersion composition was left to stand in a thermostatic bath at 60°C for one week, and then cooled to 25°C, after which it was immediately measured using a B-type viscometer with a rotor rotation speed of 100 rpm. The viscosity over time was evaluated as follows: 500mPa·s or more and 2000mPa·s or less: ◎ (excellent), more than 2000mPa·s and 3000mPa·s or less: ◯ (good), more than 3000mPa·s and 6000mPa·s or less: △ (fair), and more than 6000mPa: × (poor).

[0158] <60 degree specular gloss of carbon material dispersion composition> The gloss value was used to evaluate the degree of dispersion of the dispersed material and the surface smoothness of the coating film. The carbon material dispersion composition was applied to a PET (polyethylene terephthalate) film using a bar coater No. 7, and then dried in a hot air oven at 120°C for 5 minutes. The 60° specular gloss was measured from the surface coated with the carbon material dispersion composition using a glossmeter (VG7000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS Z8741. The 60° specular gloss was evaluated as follows: 50° or more and less than 80°: ◎ (excellent); 40° or more and less than 50°, or 80° or more and less than 90°: ◯ (good); 30° or more and less than 40°, or 90° or more: △ (fair); and less than 30°: × (poor).

[0159] <Volume resistivity of electrode film> The composite slurry is applied to the electrode using an applicator so that the weight per unit area is 20 mg / cm 2After coating on aluminum foil so that the coating was as above, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. The surface resistivity (Ω / □) of the coating after drying was then measured using a Mitsubishi Chemical Analytech Co., Ltd. Loresta GP (MCP-T610, probe: AP2 probe (RMH333)). After measurement, the surface resistivity was multiplied by the thickness of the electrode mixture layer formed on the aluminum foil to obtain the volume resistivity (Ω·cm) of the electrode film. The thickness of the electrode mixture layer was measured at three points in the electrode film using a film thickness meter (NIKON, DIGIMICRO MH-15M) and the average value was subtracted from the film thickness of the aluminum foil to obtain the volume resistivity (Ω·cm) of the electrode film. The evaluation criteria for volume resistivity were as follows: less than 8 Ω·cm: ◎ (excellent), 8 Ω·cm to less than 12 Ω·cm: ◯ (good), 12 Ω·cm to less than 15 Ω·cm: △ (passable), and 15 Ω·cm or more: × (poor).

[0160] <Peel strength of electrode film> The composite slurry is applied to the electrode using an applicator so that the weight per unit area is 20 mg / cm 2 After coating on aluminum foil so that the coating was as above, the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes. Then, the film was cut into two 90mm x 20mm rectangles with the coating direction as the long axis. Peel strength was measured using a tabletop tensile tester (Strograph E3, manufactured by Toyo Seiki Seisakusho Co., Ltd.) and evaluated by a 180-degree peel test method. Specifically, a double-sided tape (No. 5000NS, manufactured by Nitoms Co., Ltd.) measuring 100mm x 30mm was attached to a stainless steel plate, the prepared battery electrode composite layer was attached to the other side of the double-sided tape, and the layer was peeled off while being pulled from the bottom to the top at a constant speed (50mm / min). The average value of the stress at this time was taken as the peel strength. The evaluation criteria for peel strength were as follows: 1.0 N / cm or more: ◎ (excellent), 0.7 N / cm or more but less than 1.0 N / cm: ◯ (good), 0.5 N / cm or more but less than 0.7 N / cm: △ (passable), and less than 0.5 N / cm: × (poor).

[0161] <Evaluation of rate characteristics of lithium-ion secondary batteries> The laminated lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant-current constant-voltage charging (cut-off current 1.0mA (0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.2V, constant-current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 2.5V. After repeating this operation three times, constant-current constant-voltage charging (cut-off current (1.0mA0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.2V, and constant-current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage of 2.5V was reached, and the discharge capacity was calculated for each. The rate characteristic can be expressed as the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 2. (Formula 2) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) The rate characteristic evaluation was as follows: 80% or more rate characteristic was rated as ◎ (excellent), 70% or more but less than 80% rate characteristic was ◯ (good), 60% or more but less than 70% rate characteristic was △ (fair), and less than 60% rate characteristic was × (poor).

[0162] <Evaluation of high-temperature cycle characteristics of lithium-ion secondary batteries> The laminated lithium-ion secondary battery was placed in a thermostatic chamber at 45°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant-current constant-voltage charging (cutoff current 1.25mA (0.025C)) was performed with a charge current of 50mA (1C) and a charge end voltage of 4.2V, constant-current discharging was performed with a discharge current of 50mA (1C) and a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the positive electrode was discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 100th 1C discharge capacity at 45°C to the 3rd 1C discharge capacity, as shown in the following formula 3. (Formula 3) High temperature cycle characteristics = 100th 1C discharge capacity / 3rd 1C discharge capacity × 100(%) The high temperature cycle characteristics were evaluated as follows: 90% or more was rated as ◎ (excellent), 85% or more but less than 90% was rated as ○ (good), 80% or more but less than 85% was △ (fair), and less than 80% was rated as × (poor).

[0163] (Example 1-1) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 780 parts by mass of NMP and substituted with nitrogen gas. Then, the reaction vessel was heated to 80°C, 200 parts of HNBR1 was added, and the mixture was stirred until the hydrogenated nitrile butadiene rubber was completely dissolved. Then, 20 parts by mass of NaOH dispersion was added, and the mixture was stirred while adding air, and the reaction vessel was heated at 80°C for 12 hours to obtain a resin composition (R-1) containing copolymer (A1) which is copolymer (X) and an alkali metal. Based on 100% by mass of the total content of alkylene structural units and nitrile group-containing structural units in copolymer (A1), the content of alkylene structural units was 66% by mass, the content of nitrile group-containing structural units was 34% by mass, the number average molecular weight (Mn) was 18,000, the weight average molecular weight (Mw) was 30,000, and the Z average molecular weight (Mz) was 49,000. The content of other structural units constituting the copolymer (A1) was 3% by mass or less based on 100% by mass of the copolymer (A1). The alkali metal content in the resin composition was 700 ppm.

[0164] (Examples 1-2 to 1-9), (Comparative Examples 1-1 to 1-5, 1-7 to 1-9) Except for changing the conditions as shown in Table 1, the same method as in Example 1-1 was used to obtain resin compositions (R-2 to R-9) containing the copolymer (X) and the like shown in Table 1, and comparative resin compositions (RC-1 to RC-5, RC-7 to RC-9).

[0165] (Examples 1 to 10) The resin composition 9 prepared in Example 1-9 was subjected to a three-pass dispersion treatment using a high-pressure homogenizer (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) with a nozzle diameter of 0.17 mm and a pressure of 150 MPa to obtain a resin composition (R-10) containing a copolymer (E2).

[0166] (Examples 1 to 11) The resin composition 9 prepared in Example 1-9 was subjected to a five-pass dispersion treatment using a high-pressure homogenizer (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) with a nozzle diameter of 0.17 mm and a pressure of 150 MPa to obtain a resin composition (R-11) containing a copolymer (E3).

[0167] (Examples 1 to 12) HNBR1 was subjected to a five-pass dispersion treatment using a high-pressure homogenizer (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) with a nozzle diameter of 0.17 mm and a pressure of 150 MPa to obtain a resin composition (R-12) containing a copolymer (A4).

[0168] (Comparative Examples 1-6) Comparative resin composition 5 prepared in Comparative Example 1-5 was subjected to a five-pass dispersion treatment using a high-pressure homogenizer (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) with a nozzle diameter of 0.17 mm and a pressure of 150 MPa to obtain a resin composition (RC-6) containing copolymer (E5).

[0169] The contents of the alkylene structural units and the nitrile group-containing structural units, based on 100% by mass of the total content of the alkylene structural units and the nitrile group-containing structural units, are shown in Table 2. In addition, in all copolymers, the other structural units constituting the copolymer were 3% by mass or less, based on 100% by mass of the copolymer.

[0170] [Table 1]

[0171] Table 2 shows the evaluation results of the resin compositions prepared in Example 1-1 to Comparative Example 1-9.

[0172] [Table 2]

[0173] (Example 2-1) In a stainless steel container, 87.75 parts of N-methyl-2-pyrrolidone (NMP) and 8.75 parts of resin composition (R-1) were added and stirred using a disperser. Then, 3.5 parts of carbon nanotubes (JEIO, JENOTUBE6A) were weighed out and added while stirring with a disperser. A fine emulsion screen was attached to a high shear mixer (L5M-A, SILVERSON), and the mixture was dispersed in a batch manner at a speed of 9000 rpm until the entire mixture became uniform and the dispersion particle size was 200 μm or less using a grind gauge. The mixture was then passed through a high magnetic force mag filter (Eishin, surface magnetic flux density 17000 gauss) to prepare a carbon material pre-dispersion composition. Thereafter, the carbon material pre-dispersion composition was sent and subjected to a circulation type dispersion treatment (beads filling rate 80%, peripheral speed 13 m / s) with a residence time of 10 minutes using a bead mill (Mugen Flow (registered trademark) manufactured by Ashizawa Finetech Co., Ltd.) filled with zirconia beads having a diameter of 1.0 mm. The number of circulations was 50. Next, the liquid to be dispersed was supplied to a high-pressure homogenizer (Starburst Lab manufactured by Sugino Machine Co., Ltd.) and a 15-pass type dispersion treatment was performed. The dispersion treatment was carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The liquid to be dispersed was then supplied to an electromagnet (manufactured by Taiho Magnetics, EMF-100S, magnetic flux density 16,000 gauss, spatial volume 1.7 L, electromagnet equipped with 31 grid screens with a diameter of 10 cm and a thickness of 1.3 cm) and subjected to a three-pass treatment. After that, the liquid was passed through two depth filters (manufactured by 3M, PP nonwoven fabric depth cartridge NT-T series, filtration accuracy 20 μm) installed in series to obtain a carbon material dispersion composition 1.

[0174] (Examples 2-2 to 2-16), (Comparative Examples 2-1 to 2-9) Carbon material dispersion compositions 2 to 16 and comparative carbon material dispersion compositions 1 to 9 were obtained in the same manner as in Example 2-1, except that the dispersion conditions, carbon material, resin composition, amount of resin composition added, and NMP listed in Table 3 were changed.

[0175] [Table 3]

[0176] Table 4 shows the evaluation results of the carbon material dispersion compositions prepared in Examples 2-1 to 2-16 and Comparative Examples 2-1 to 2-9.

[0177] [Table 4]

[0178] (Example 3-1) Capacity 150cm 3 Into the plastic container, 18.8 parts by mass of NMP solution in which 8% by mass of PVDF (polyvinylidene fluoride, Solvey, Solef#5130) was dissolved, and 14.5 parts by mass of NMP were weighed. Then, 11.4 parts by mass of carbon material dispersion composition (carbon material dispersion composition 1) was added, and the mixture was stirred at 2000 rpm for 30 seconds using a rotation-revolution mixer (Awatori Rentaro, ARE-310). Then, 98.1 parts by mass of positive electrode active material (BASF Toda Battery Materials, LLC, HED (registered trademark) NCM-111 1100) was added, and the mixture was stirred at 2000 rpm for 2.5 minutes using a rotation-revolution mixer (Awatori Rentaro, ARE-310) to obtain a composite slurry (composite slurry 1).

[0179] Next, the composite slurry (composite slurry 1) was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode was 20 mg / cm2. 2 After coating on an aluminum foil so that the coating was as follows: the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode film (electrode film 1). The electrode film (electrode film 1) was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 1). The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.1 g / cc.

[0180] (Examples 3-2 to 3-5, Examples 3-8 to 3-16) (Comparative Examples 3-1 to 3-9) As shown in Table 5, except that carbon material dispersion compositions 2 to 16 and comparative carbon material dispersion compositions 1 to 9 were used instead of carbon material dispersion composition 1, composite slurries 2 to 16, comparative composite slurries 1 to 9, electrode films 2 to 16, comparative electrode films 1 to 9, positive electrodes 2 to 16, and comparative positive electrodes 1 to 9 were obtained in the same manner as in Example 3-1.

[0181] (Examples 3 to 6) Capacity 150cm 3 Into the plastic container, 18.8 parts by mass of NMP solution in which 8% by mass of PVDF (polyvinylidene fluoride, Solvey, Solef#5130) was dissolved, and 18.9 parts by mass of NMP were weighed. Then, 7.1 parts by mass of carbon material dispersion composition (carbon material dispersion composition 1) was added, and the mixture was stirred at 2000 rpm for 30 seconds using a rotation-revolution mixer (Awatori Rentaro, ARE-310). Then, 98.1 parts by mass of positive electrode active material (BASF Toda Battery Materials, LLC, HED (registered trademark) NCM-111 1100) was added, and the mixture was stirred at 2000 rpm for 2.5 minutes using a rotation-revolution mixer (Awatori Rentaro, ARE-310) to obtain a composite slurry (composite slurry 6).

[0182] Next, the composite slurry (composite slurry 6) was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode was 20 mg / cm2. 2 After coating on an aluminum foil so that the coating was as follows: the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode film (electrode film 6). The electrode film (electrode film 1) was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 6). The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.1 g / cc.

[0183] (Examples 3 to 7) Capacity 150cm 3Into the plastic container, 18.8 parts by mass of NMP solution in which 8% by mass of PVDF (polyvinylidene fluoride, Solvey, Solef#5130) was dissolved, and 21.6 parts by mass of NMP were weighed. Then, 5.0 parts by mass of carbon material dispersion composition (carbon material dispersion composition 1) was added, and the mixture was stirred at 2000 rpm for 30 seconds using a rotation-revolution mixer (Awatori Rentaro, ARE-310). Then, 97.5 parts by mass of positive electrode active material (BASF Toda Battery Materials, LLC, HED (registered trademark) NCM-111 1100) was added, and the mixture was stirred at 2000 rpm for 2.5 minutes using a rotation-revolution mixer (Awatori Rentaro, ARE-310) to obtain a composite slurry (composite slurry 7).

[0184] Next, the composite slurry (composite slurry 7) was applied to the electrode using an applicator so that the weight per unit area of ​​the electrode was 20 mg / cm2. 2 After coating on an aluminum foil so that the coating was as follows: the coating was dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode film (electrode film 7). The electrode film (electrode film 1) was then rolled using a roll press (3t hydraulic roll press, manufactured by Sun Metals) to obtain a positive electrode (positive electrode 6). The weight per unit area of ​​the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.1 g / cc.

[0185] Table 5 shows the evaluation results of the electrode films produced in Examples 3-1 to 3-3-16 and Comparative Examples 3-1 to 3-9.

[0186] [Table 5]

[0187] (Example 4-1) The positive electrode (positive electrode 1) and the standard negative electrode were punched out to 45 mm x 40 mm and 50 mm x 45 mm, respectively, and the separator (porous polypropylene film) between them was inserted into an aluminum laminate bag and dried in an electric oven at 60°C for 1 hour. After that, in a glove box filled with argon gas, 2 mL of electrolyte (a non-aqueous electrolyte prepared by mixing ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a ratio of 1:1:1 (volume ratio) and adding 2 parts by mass of VC (vinylene carbonate) as an additive to 100 parts by mass of the mixed solvent, and then dissolving LiPF6 at a concentration of 1M) was injected, and the aluminum laminate was sealed to prepare a laminated lithium-ion secondary battery (secondary battery 1).

[0188] (Examples 4-2 to 4-16, Comparative Examples 4-1 to 4-9) Laminated lithium ion secondary batteries (secondary battery 2) to (comparative secondary battery 9) were produced in the same manner as in the production of the laminated lithium ion secondary battery (secondary battery 1), except that the positive electrode was changed as shown in Table 6.

[0189] [Table 6]

[0190] In the above examples, a resin composition was used that contains copolymer (X) and an alkali metal in an amount of 50 ppm or more and less than 10,000 ppm, and that has a resistivity of 5,000 Ω·cm or more and 25,000 Ω·cm or less when the resin composition is adjusted to a copolymer content of 8 mass% with N-methyl-2-pyrrolidone. In the examples, a lithium ion secondary battery was obtained that had excellent viscosity stability over time and excellent secondary battery characteristics, particularly high-temperature cycle characteristics, compared to the comparative examples. Therefore, it has become clear that the present invention can provide a lithium ion secondary battery having high capacity, high output, and high durability that are difficult to achieve with conventional carbon material dispersion compositions. A vehicle having the lithium ion secondary battery of the present invention has high charge / discharge performance and excellent high-temperature cycle characteristics, and therefore a vehicle with high safety and improved fuel economy can be obtained.

[0191] Although the present invention has been described above with reference to the embodiment, the present invention is not limited to the above. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the invention.

Claims

1. A resin composition containing a copolymer (X) having an alkylene structural unit and a nitrile group-containing structural unit, and an alkali metal, The content of the alkali metal is 50 ppm or more and less than 10,000 ppm, The Z-average molecular weight of the copolymer (X) is 20,000 or more and 250,000 or less, The ratio (Mz / Mw) of the Z-average molecular weight (Mz) to the weight-average molecular weight (Mw) of the copolymer (X) is 1.63 or more; A resin composition, characterized in that the resistivity of the resin composition when the nonvolatile content is adjusted to 8 mass % with N-methyl-2-pyrrolidone is 5,000 Ω cm or more and 25,000 Ω cm or less.

2. 2. The resin composition according to claim 1, wherein the Z-average molecular weight of the copolymer (X) is 20,000 or more and 200,000 or less.

3. 2. The resin composition according to claim 1, wherein the ratio (Mz / Mw) of the Z-average molecular weight (Mz) to the weight-average molecular weight (Mw) of the copolymer (X) is 2.0 or less.

4. A carbon material dispersion composition comprising the resin composition according to any one of claims 1 to 3 and a carbon material.

5. A composite slurry comprising the carbon material dispersion composition according to claim 4 and an active material.

6. An electrode film formed by coating the composite slurry according to claim 5 .

7. A secondary battery comprising an electrode having the electrode film according to claim 6 and an electrolyte.

8. A vehicle comprising the secondary battery according to claim 7.

Citation Information

Patent Citations

  • Fine carbon fiber dispersion liquid and method for producing the same

    JP2014181140A

  • CARBON NANOTUBE DISPERSION AND METHOD FOR MANUFACTURING SAME

    JP2018522803A

  • Conductive material dispersion and utilization thereof

    JP2020187866A

  • Dispersant, conductive material dispersion, and slurry for electrode film

    JP2021122751A

  • Pre-dispersant composition, electrode and secondary battery including the same

    JP2022536304A